Adenomatous hyperplasia induced by chronic cherry pit retention mimicking an endobronchial tumor-case series and systematic review of literature - Oruqaj, Gani; Krombach, Gabriele; Gattenloehner, Stefan; Herold, Susanne; Vadász, István; Seeger, Werner; Tello, Khodr; Hecker, Matthias (Frontiers in Medicine, 2024)
Introduction Endobronchial foreign body aspiration is not common in adults, but it is a life-threatening event. Recurrent pneumonias by chronic retention of foreign body often lead to initial medical presentation of the patient. However, lymphoplasmacellular bronchitis with adenomatous hyperplasia and squamous epithelium metaplasia with complete or partial blockage of lobar bronchus mimicking lung tumor is rare in literature, and this particular condition is often misdiagnosed. Case presentation we report our experience in the diagnostic and management of two elderly patients with recurrent pneumonia, admitted in hospital for further examination. In both patients, with no history of aspiration, the cherry pit was detected during bronchoscopy and recanalization with flexible cryoprobe, surrounded by purulent secretion, occluding completely the right upper lobe in the first case, and partially the left lower lobe associated with persistent actinomycosis in the second case, with signs of local inflammation, bronchial adenomatous hyperplasia mimicking lung tumor at initial bronchoscopic examination. Histology showed a lymphoplasmacellullar bronchitis with adenomatous hyperplasia and squamous epithelium metaplasia because of chronic retention of foreign body. Conclusion Bronchoscopy examination should be considered in cases where there is an unresolved chronic cough with recurrent pneumonia or persistent actinomycosis in patients with high risk. Cryoprobe is a safe and feasible approach for treatment of airway obstructions due to chronic foreign body retention. Furthermore, relevant findings are discussed here, along with a review of the pathologic alterations and treatment modalities seen in chronic retention of foreign body and airway injury.